Heterologous Immune Responses to Influenza Vaccine in Kidney Transplant Recipients. Issue 1 (9th August 2016) - Kumar, D.; Ferreira, V. H.; Campbell, P.; Hoschler, K.; Humar, A.
Abstract : Influenza vaccine is known to have suboptimal immunogenicity in transplant recipients. Despite this, influenza vaccine may have the added benefit of inducing a cross‐reactive immune response to viral strains not found in the vaccine. This is termed "heterologous immunity" and has not been assessed previously in transplant patients. Pre‐ and postvaccination sera from kidney transplant recipients (n = 60) immunized with the 2012–2013 adjuvanted or nonadjuvanted influenza vaccine underwent testing by hemagglutination inhibition assay for strains not present in vaccine: A/New Caledonia/20/99 (H1N1), A/Texas/50/2012 (H3N2) and B/Brisbane/60/2008. The geometric mean titer of antibody to heterologous strains increased after vaccine (H1N1: 80.0 to 136.1, p < 0.001; H3N2: 23.3 to 77.3, p < 0.001; B: 13.3 to 19.5, p < 0.001). Seroconversion rates were 16.7%, 41.7%, and 13.3%, respectively. No differences in heterologous response were seen in the adjuvanted versus nonadjuvanted groups. Patients were more likely to seroconvert for a cross‐reactive antigen if they seroconverted for the specific vaccine antigen. Seroconversion to heterologous A/H3N2, for example, was 84.0% for homologous H3N2 seroconverters versus 11.4% for nonseroconverters (p < 0.001). This study provides novel evidence that transplant recipients are able to mount significant cross‐protective responses to influenza vaccine that may be an additional, previously unknown benefit of immunization. Abstract : Transplant recipients who respond to the influenza vaccine also have heterologous responses to influenza strains not included in the vaccine, suggesting the formation of cross‐protective immunity as an additional benefit of vaccination.